2012
DOI: 10.3389/fpsyg.2011.00391
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Motion Capturing Ambiguous Visual Motion

Abstract: In this study, it is demonstrated that moving sounds have an effect on the direction in which one sees visual stimuli move. During the main experiment sounds were presented consecutively at four speaker locations inducing left or rightward auditory apparent motion. On the path of auditory apparent motion, visual apparent motion stimuli were presented with a high degree of directional ambiguity. The main outcome of this experiment is that our participants perceived visual apparent motion stimuli that were ambig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
(46 reference statements)
1
13
1
Order By: Relevance
“…This finding is in contrast to previous findings demonstrating that rightward moving auditory stimuli could capture ambiguous visual motion stimuli, but that leftward moving stimuli did not (Alink et al, 2012). In our study, we made use of pre-recorded leftward moving auditory motion stimuli that were digitally reversed so that they were perceived as moving rightward.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This finding is in contrast to previous findings demonstrating that rightward moving auditory stimuli could capture ambiguous visual motion stimuli, but that leftward moving stimuli did not (Alink et al, 2012). In our study, we made use of pre-recorded leftward moving auditory motion stimuli that were digitally reversed so that they were perceived as moving rightward.…”
Section: Discussioncontrasting
confidence: 99%
“…This interpretation of our finding is consistent with the maximum likelihood estimation view of multisensory perception (Ernst and Banks, 2002; De Gelder and Bertelson, 2003; Ernst and Bülthoff, 2004) as well as findings in research on multisensory integration at large demonstrating that auditory stimuli can have a profound influence on visual perception if the auditory stimuli are sufficiently reliable (Driver and Spence, 2000; Shimojo and Shams, 2001; Ghazanfar and Schroeder, 2006; Alink et al, 2012). In the case of motion perception in particular, for example, it has been demonstrated that auditory spatial information provided by alternating sound locations can cause a static visual stimulus to be perceived as moving in an illusion referred to as the sound-induced visual motion illusion (Hidaka et al, 2011b) and that auditory motion stimuli can capture ambiguous visual motion and change the perceived apparent motion of visual stimuli in the same direction as the moving auditory stimuli (Alink et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations